KINETIC AND THERMODYNAMIC STUDIES OF PURIFIED PROTEIN ISOLATED FROM EUPHORBIA TIRUCALLI LATEX - Sharma, Tripti; Dash, Priyanka; Das, Debajyoti; Ghosh, Goutam (Asian Journal of Pharmaceutical and Clinical Research, 2014)
The kinetic and thermodynamic parameters of an isolated protein from the latex of Euphorbia tirucalli were studied in this work. The isolated protein was named as Euphorbian T and was found to possess proteolytic activity through milk clotting and caseinolytic digestion process. The electrophoresis analysis of purified Euphorbian T was carried out using sodium dodecyl sulfate-polyacrylamide gel. The aminoacids of Euphorbian T were appeared in different bands of 36.5, 39, 44 and 50 Kda. The effect of pH, temperature, and concentration of substrate on proteolytic activity of Euphorbian T was examined. The maximum proteolytic activity of this protein was obtained at pH 6. The temperature t(max) for maximum activity range of the enzyme was found to be 65°C. The Kinetics parameters i.e., Km and Vmax of the purified protein with milk and caesin as substrate, were estimated using Lineweaver–Burk plot and were found to be 4 mg/dl, 0.21 U/mg and 2 mg/dl, 1.03 U/mg, respectively. Thermodynamic constants i.e., activation energy (Ea), change in enthalpy (ΔH) and change in entropy (ΔS) and free energy changes (ΔG) of Euphorbian T for milk were calculated using Arrhenius plot and were found to be 1.58 kcal/mol, 1.54 kcal/mol, −10.46 cal mol/deg and 18.87 kcal/mol respectively, whereas with the substrate caesin, the activation energy (Ea), change in enthalpy (ΔH) and change in entropy (ΔS) and free energy changes (ΔG) were calculated as 1.12 kcal/mol, 1.08 kcal/mole, −16.24 cal mol/deg and 16.34 kcal/mol, respectively. Keywords: Euphorbia tirucalli, Euphorbian T, Milk clotting, Caseinolytic.